2016
DOI: 10.1186/s12931-016-0462-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired anti-inflammatory action of glucocorticoid in neutrophil from patients with steroid-resistant asthma

Abstract: BackgroundSteroid resistant (SR) asthma is characterized by persistent airway inflammation that fails to resolve despite treatment with high doses of corticosteroids. Furthermore, SR patient airways show increased numbers neutrophils, which are less responsive to glucocorticoid. The present study seeks to determine whether dexamethasone (DEX) has different effect on neutrophils from steroid sensitive (SS) asthmatics compared to SR asthmatics.MethodsAdults with asthma (n = 38) were classified as SR or SS based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…The persistent neutrophilia in asthma should not own to the use of glucocorticoids, because glucocorticoids exerted the same effects on the apoptosis of neutrophils from steroid-sensitive asthma and steroid-resistant asthma with increased neutrophils in airway, as shown in our study [18] . In addition, Uddin and colleagues indicated that unresolved airways neutrophilia in severe asthma were the result of their prolonged survival promoted by factors released by inflammatory and structural cells of the airways [58] .…”
Section: Severity and Airflow Obstructionsupporting
confidence: 67%
See 3 more Smart Citations
“…The persistent neutrophilia in asthma should not own to the use of glucocorticoids, because glucocorticoids exerted the same effects on the apoptosis of neutrophils from steroid-sensitive asthma and steroid-resistant asthma with increased neutrophils in airway, as shown in our study [18] . In addition, Uddin and colleagues indicated that unresolved airways neutrophilia in severe asthma were the result of their prolonged survival promoted by factors released by inflammatory and structural cells of the airways [58] .…”
Section: Severity and Airflow Obstructionsupporting
confidence: 67%
“…This phenomenon could be explained by increased chemotactic factors, such as IL-8, TNFα, LTB4 and IL-17A, in the circulation of patients suffering from asthma [6,[14][15][16][17] . Our previous study also demonstrated that neutrophils from steroid-resistant asthma released more IL-8 at the presence of asthmatics serum, which might contribute to additional recruitment and activation of neutrophils in a positive feedback manner [18] . Moreover, Lavinskiene et al reported that the migration of neutrophils to the airways after allergen challenge was increased in asthmatic comparing to non-asthmatic subjects, because they were more sensitive to IL-8 stimulation [19] .…”
Section: Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…This profile develops due to an increased neutrophil influx, overcoming the classic asthmatic eosinophilia . It is already established that neutrophils are more resistant to glucocorticoids, contributing to the severity of the disease . Several mechanisms have been associated with this shift, as increased NLRP3 inflammasome activation, DC activation failure, macrophage profile modification and lower TSLP levels …”
Section: Introductionmentioning
confidence: 99%